EL PERMISO POR LACTANCIA DIEZ AÑOS DESPUÉS DE LA LEY DE IGUALDAD - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
The widespread incorporation of women into the common productive world, the equalization of functions among men and women, the locative mobility inherent to numerous jobs, the quality of artificial feeding for babies, the preservation of business productivity, the avoidance of indirect discrimination , the demands of health and hygiene, flexibility in the organization of working time. All these factors, in a list that could easily be increased without any effort, are projected in the regulation of a figure as traditional as plagued by interpretative doubts at the time of putting it into practice. The pause or permission for breastfeeding is the institution object of study in the following pages, whose formal object is constituted by the special attention to the doctrine emanating from the Courts. After more than ten years of validity of the Organic Law for Effective Equality of Women and Men (LOI) and recently seated several interpretative criteria by our Courts, it seems an appropriate time to make a balance on the subject.